Determinan Nilai Perusahaan Publik di Indonesia dan Filipina dengan Kepemilikan Institusional sebagai Pemoderasi - Mia Julia Putri; Nurmala Ahmar (Jurnal Riset Akuntansi & Perpajakan (JRAP), 2019)
ABSTRACT Firm value is one the management's standard in managing the business. This study aims to scrutinize about determination value of enterprise public in indonesia and the philippines to the ownership of institutional as a moderator. Sample used in this research was the company into an LQ45 index in Indonesia and an PSEi30 index in the Philippines. Technique analysis the data used was structural equation modelling-partial least square (SEM-PLS) using warppls 6.0. It is also done analysis multigroup to see if there is a difference in the influence of profitability, the solvability and the size of the company on the companies in Indonesia and the Philippines. The results of testing shows that its satisfactory profitability as to depend on the value of enterprise in Indonesia and the Philippines. The solvability has not been affecting the value of enterprise in Indonesia and the Philippines. For variables the size of the company, or is the size of the striking result. It is to depend on the value of enterprise in the Philippines, while in Indonesia do not affect the size of the company. Following the completion of variable moderation or testing by adding the results showed that in Indonesia, institutional ownership capable of moderating influence on the perceived value of the company profitability, while in the Philippines ownership of moderating the influence of institutional capable of reducing the size of the company on the perceived value of the company. The results of the analysis multigroup show there is a difference of determination value of enterprise in Indonesia and the Philippines to the ownership of institutional as an moderation variable. ABSTRAK Studi ini bertujuan untuk meneliti mengenai determinasi nilai perusahaan publik di Indonesia dan Filipina dengan kepemilikan institusional sebagai pemoderasi. Sampel yang digunakan dalam penelitian ini adalah perusahaan yang masuk ke dalam indeks LQ45 di Indonesia dan indeks PSEi30 di Filipina. Teknik analisis data yang digunakan adalah Structural Equation Modelling-partial Least Square (SEM-PLS) dengan menggunakan program WarpPLS 6.0. analisis multigrup untuk mengetahui apakah ada perbedaan pengaruh profitabilitas, solvabilitas dan ukuran perusahaan terhadap nilai perusahaan di Indonesia dan Filipina. Hasil pengujian menunjukkan bahwa profitabilitas berpengaruh terhadap nilai perusahaan di Indonesia dan Filipina. Solvabilitas tidak berpengaruh terhadap nilai perusahaan di Indonesia dan Filipina. Untuk variabel ukuran perusahaan, hasil yang didapatkan adalah ukuran berpengaruh terhadap nilai perusahaan di Filipina, sedangkan di Indonesia ukuran perusahaan tidak berpengaruh. Setelah dilakukan pengujian dengan menambahkan variabel moderasi didapatkan hasil bahwa di Indonesia, kepemilikan institusional mampu memoderasi pengaruh profitabilitas terhadap nilai perusahaan, sedangkan di Filipina kepemilikan institusional mampu memoderasi pengaruh profitabilitas dan ukuran perusahaan terhadap nilai perusahaan. Hasil analisis multigrup menunjukkan terdapat perbedaan determinasi nilai perusahaan di Indonesia dan Filipina dengan kepemilikan institusional sebagai pemoderasi. JEL Classification: M40, G30